STUDY ON CONSTITUTIVE MODEL AND MECHANICAL PROPERTIES OF 7003 ALUMINUM ALLOY - XU Yun; HU YuMei; ZHAO WeiMin; LI Jie (Jixie qiangdu, 2019)
The stress-strain curves and fracture characteristics of 7003 aluminum alloy under different stress triaxiality and strain rates were obtained by dynamic and static tests,and the constitutive model of Johnson-Cook material with sensitive strain rate was fitted by the experimental results. The experimental results show that the fracture process of 7003 aluminum alloy has strain rate sensitivity,and the fracture strain decreases with the increase of stress triaxiality. The whole fracture process of 7003 aluminum alloy was simulated by LS-DYNA software,and the simulation results were in good agreement with the experiment.